Effect of the implantoplasty techniques on the fracture resistance of dental implants. Systematic review and meta-analysis - Pissu, Giovanni; Flores-Fraile, Javier; Zubizarreta-Macho, Álvaro; Montiel-Company, José María; Lobo-Galindo, Ana Belén (Frontiers in Dental Medicine, 2025)
The aim of this systematic review and meta-analysis was to analyze and compare the effect of diamond drill, tungsten carbide drill and ultrasound tips for implantoplasty procedures on the fracture resistance of dental implants affected by periimplant disease. Materials and methodsThis systematic review of the scientific literature and meta-analysis was carried out based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), analyzing all studies that evaluated the fracture resistance of dental implants submitted to implantoplasty through diamond drill, tungsten carbide drill and ultrasound tips for implantoplasty procedures, comparing with the fracture resistance values of non-treated dental implants. A total of 4 databases were searched in the literature: Pubmed, Scopus, Cochrane and Web of Science. After eliminating duplicate articles and applying certain inclusion criteria, a total of 9 articles were selected and compared using the random effects model and inverse variance method. The significance of the effect size was measured with the z test, the heterogeneity using the Q test and the I2 and publication bias was analyzed using the trim-and-fill methodResultsThe difference in means between the treatment and control groups was estimated as the effect size, obtaining a statistically significant difference of −232.01 MPa., with a 95% confidence interval of the difference between −417.3 and −44.71 (z test = −2.43; p-value = 0.015). The meta-analysis has presented high heterogeneity with an I2 = 99.3% and a Q test = 2,195.7; p-value < 0.001. No significant differences were found between the three subgroups with the Q test = 0.20: p-value = 0.903.Conclusionsthe tungsten carbide drills resulted in less fracture resistance loss than the diamond and tungsten carbide drills for the dental implants submitted to implantoplasty procedures. Systematic Review Registration: [http://www.prisma-statement.org], identifier [INPLASY202460018].